Fast software encryption 13th international workshop, FSE 2006, Graz, Austria, March 15-17, 2006, revised selected papers - FSE 2006 (Lecture notes in computer science, 2006)
Fast Software Encryption (FSE) 2006 is the 13th in a series of workshops on symmetric cryptography. It has been sponsored for the last ?ve years by the International Association for Cryptologic Research (IACR), and previous FSE workshops have been held around the world: 1993 Cambridge, UK 1994 Leuven, Belgium 1996 Cambridge, UK 1997 Haifa, Israel 1998 Paris, France 1999 Rome, Italy 2000 New York, USA 2001 Yokohama, Japan 2002 Leuven, Belgium 2003 Lund, Sweden 2004 New Delhi, India 2005 Paris, France The FSE workshop is devoted to research on fast and secure primitives for symmetric cryptography, including the design and analysis of block ciphers, stream ciphers, encryption schemes, analysis and evaluation tools, hash fu- tions, and message authentication codes. This year more than 100 papers were submitted to FSE for the ?rst time. After an extensive review by the ProgramCommittee, 27 papers were presented at the workshop. Of course, the programwould not have been complete without the invited speaker, and the presentation by Eli Biham on the early history of di?erential cryptanalysis was particularly appreciated by workshop attendees. Stream ciphers I -- Cryptanalysis of achterbahn -- Cryptanalysis of grain -- Cryptanalysis of the stream cipher DECIM -- Block ciphers -- On feistel structures using a diffusion switching mechanism -- Pseudorandom permutation families over abelian groups -- A Zero-dimensional Gröbner basis for AES-128 -- Hash functions I -- Cryptanalysis of the Full HAVAL with 4 and 5 Passes -- Collisions and near-collisions for reduced-round tiger -- Analysis of step-reduced SHA-256 -- Analysis -- Improved linear distinguishers for SNOW 2.0 -- Reducing the space complexity of BDD-based attacks on keystream generators -- Breaking the ICE – Finding multicollisions in iterated concatenated and expanded (ICE) Hash functions -- Proposals -- A new dedicated 256-bit hash function: FORK-256 -- Some plausible constructions of double-block-length hash functions -- Provably secure MACs from differentially-uniform permutations and AES-based implementations -- Hash functions II -- Searching for differential paths in MD4 -- A study of the MD5 attacks: Insights and improvements -- The impact of carries on the complexity of collision attacks on SHA-1 -- Modes and models -- A New mode of encryption providing a tweakable strong pseudo-random permutation -- New blockcipher modes of operation with beyond the birthday bound security -- The ideal-cipher model, revisited: an uninstantiable blockcipher-based hash function -- Implementation and bounds -- How far can we go on the x64 processors? -- Computing the algebraic immunity efficiently -- Upper bounds on algebraic immunity of boolean power Functions -- Stream ciphers II -- Chosen-ciphertext attacks against MOSQUITO -- Distinguishing attacks on the stream cipher Py -- Resynchronization attacks on WG and LEX.